
I'm not sure what should be the proper solution. Perhaps to change the laws to: return x >> mzero = mzero (v >> mzero) >>= f = (v >> mzero)` That is, if an expression ends with `mzero`, it behaves like `mzero`.
These laws are redundant with existing laws. The first: return x >> z = z Is true forall x and z, and can be proven by just the monad laws. The second: (v >> mzero) >>= f = (v >> mzero) Can be proven by the associativity of monadic operations: (v >> mzero) >>= f = v >> (mzero >>= f) And the other MonadPlus law already states that (mzero >>= f) = mzero. So I don't think any new laws are needed. I just think the (v >> mzero = mzero) law should be removed, or else a *lot* of instances of MonadPlus need to come with a disclaimer that they are not law-abiding. -- Dan Burton